Diretrizes para a concepção de projetos de sistema fotovoltaico conectado à rede em residências de médio padrão na cidade de Pato Branco - Paraná - Santos, Erica Kelly Schllemer dos (2018)
The photovoltaic system connected to the building and connected to the grid is a type of urban residential, commercial and industrial electricity generating source considered ideal in a country with solar radiation conditions such as Brazil. With the purpose of familiarization, this work will present a brief description of photovoltaic solar energy, the types of photovoltaic systems and their main components. Subsequently, the regulatory regulations related to this type of energy generation will be discussed, as well as a brief history of sustainability, and the panorama of photovoltaic solar energy in Brazil and in the world. The basic requirements for photovoltaic systems projects and the main internet softwares that carry out the sizing and simulation of these will be described below. Finally, the calculation of a system for a medium-standard residence for the city of Pato Branco, Paraná, will be presented and the budgets will be made at local companies to know the cost of the system and the time of return of the investment.